A cantilever approach to estimate bending stiffness of buildings affected by tunnelling - Haji, Twana; Marshall, Alec M.; Tizani, Walid (Elsevier, 2018)
The evaluation of the effect of tunnel construction on buildings is a problem being faced by engineers around the world. Building bending stiffness is an important parameter in tunnel-soil-structure interaction analyses. The construction of a new tunnel influences an existing building via induced ground movements, and the existence of a building also affects ground displacements due to tunnelling via its stiffness and weight. The magnitude of the effect depends on the properties of the building and foundation as well as the complex soil-structure interactions that occur. In this paper, an approach is proposed in which the building response to tunnelling is related to the bending of a cantilever beam and empirical-type relationships are developed to predict building bending stiffness. This approach is relevant to cases where the building is perpendicular to the tunnel axis and its nearest edge does not overlap more than half of the tunnel cross-section. Rigorous finite element analyses are used to evaluate the response of buildings to ground displacements and expressions are provided which relate three-dimensional building bending stiffness to a simple beam theory expression. The results show that lower storeys have a proportionally higher stiffness effect than higher storeys. In addition, the parameters that affect the global behaviour of the building, such as component stiffness and geometry, are studied. The suggested approach provides a relatively quick and easy way of accurately evaluating building bending stiffness for use within tunnel-soil structure interaction analyses.